Art Walks and their Impact on the Attractiveness of the City : Case Study: From Chillida to Plensa on Madrid's Paseo de la Castellana - Casado de Prada, Manuela; Fernández Añez, María Victoria; Ondiviela García, Jose Antonio (Street Art & Urban Creativity, 2025)
Art walks play a vital role in fostering shared values and enhancing a city's unique character. This study examines the artistic sculptural route along the Paseo de la Castellana in Madrid, specifically the stretch from Plaza de Colón to Plaza de San Juan de la Cruz, assessing its influence on the city's attractiveness and its impact on the life of its citizens. The itinerary is interpreted in the light of López Quintás' philosophy of realms, evaluating its contribution to the city's branding and personality, both of which are crucial to urban attractiveness. A temporal framework is employed to explore this analysis, structured into three realms: Urban Identity (Past), Urban Dynamism (Present), and Urban Strategy (Future). The findings reveal that such artistic itineraries play a significant role in shaping the identity and magnetism of a city, generating value and enhancing the quality of life for its inhabitants.